Public expenditures on education and health in Russian Federation before and during the global crisis - Irina Sinitsina (Center for Social and Economic Research (CASE), 2011)
This paper explores the effects that the global financial crisis of 2008 - 2010 had on the funding and performance of the healthcare and education sectors in the Russian Federation (RF). Both education and healthcare expenditures increased in terms of total general government (GG) spending relative to GDP, partly as a result of reduced GDP. The crisis induced further centralization by increasing both the role of the federal budget in funding social services and the dependence of regions on federal transfers, but it did not result in enhanced resource allocation or more effective public spending. By revealing the inefficiencies that accumulated in education and healthcare financing and management throughout the 2000s, the crisis exposed acute funding shortages in contrast to the government's stated goals and an urgent need for reform in these sectors. The impact of the financial crisis on the delivery of education and health services appeared to be delayed and was mitigated by the resources accumulated during the pre-crisis boom. The paper concludes with several recommendations for the RF public service sector concerning improvements in the inter-governmental transfer system through increasing transparency and introducing performance-oriented budgeting.
Keywords: E62; H50; H51; H52; I18; I22; 330; Fiscal policy; Russian Federation; Education financing; Health financing; Global economic crisis; Öffentliche Finanzen; Öffentliche Ausgaben; Finanzpolitik; Bildungswesen; Bildungsfinanzierung; Gesundheitswesen; Gesundheitskosten; Finanzkrise; Russland